Push-Pull Zinc Porphyrins as Light-Harvesters for Efficient Dye-Sensitized Solar Cells - Lu, Jianfeng; Liu, Shuangshuang; Wang, Mingkui (Frontiers in Chemistry, 2018)
Dye-sensitized solar cell (DSSC) has been attractive to scientific community due to its eco-friendliness, ease of fabrication, and vivid colorful property etc. Among various kinds of sensitizers, such as metal-free organic molecules, metal-complex, natural dyes etc., porphyrin is one of the most promising sensitizers for DSSC. The first application of porphyrin for sensitization of nanocrystaline TiO2 can be traced back to 1993 by using [tetrakis(4-carboxyphenyl) porphyrinato] zinc(II) with an overall conversion efficiency of 2.6%. After 10 years efforts, Officer and Grätzel improved this value to 7.1%. Later in 2009, by constructing porphyrin sensitizer with an arylamine as donor and a benzoic acid as acceptor, Diau and Yeh demonstrated that this donor-acceptor framwork porphyrins could attain remarkable photovoltaic performance. Now the highest efficiencies of DSSC are dominated by donor-acceptor porphyrins, reaching remarkable values around 13.0% with cobalt-based electrolytes. This achievement is largely contributed by the structural development of donor and acceptor groups within push-pull framwork. In this review, we summarized and discussed the developement of donor-acceptor porphyrin sensitizers and their applications in DSSC. A dicussion of the correlation between molecular structure and the spectral and photovoltaic properties is the major target of this review. Deeply dicussion of the substitution group, especially on porphyrin's meso-position were presented. Furthermore, the limitations of DSSC for commercialization, such as the long-term stability, sophisticated synthesis procedures for high efficiency dye etc., have also been discussed.